Transmodalidade em/e processos de produção: mudando disposições e práticas - Shipka, Jody (2021)
In this work, Jody Shipka reflects on the multisemiotic nature of compositional practices based on a transmodal approach. The author calls attention to the need for changing dispositions and practice to embrace the complex diversity of processes, overlaps, dialogues, semiosis, agencies, and materialities involved in the meaning-making process. Moving beyond graphocentric practices, Shipka argues for the work with diversity as a resource for making and negotiating meanings, in order to expand students’ rhetorical  awareness  and  develop  their compositional fluency, allowing for the reflection about the variety of conventions, technologies, materialities and practices mobilized in the compositional process.